Less efficient pattern separation may contribute to age-related spatial memory deficits - Holden, Heather M.; Gilbert, Paul E. (Frontiers in Aging Neuroscience, 2012)
Spatial memory deficits have been well documented in older adults and may serve as an early indicator of mild cognitive impairment or Alzheimer’s disease in some individuals. Pattern separation is a critical mechanism for reducing potential interference among similar memory representations to enhance memory accuracy. A small but growing literature indicates that spatial pattern separation may become less efficient as a result of normal aging, possibly due to age-related changes in subregions of the hippocampus. This decreased efficiency in spatial pattern separation may be a critical processing deficit that could be a contributing factor to spatial memory deficits and episodic memory impairment associated with aging. The present paper will review recently published studies in humans, nonhuman primates, and rodents that have examined age-related changes in spatial pattern separation. The potential basic science, translational, and clinical implications from these studies are discussed to illustrate the need for future research to further examine the relationship between spatial pattern separation and brain changes associated with aging and neurodegenerative disease.